Regional Organizations and Their Responses to Coups Measures, Motives and Aims. - Hohlstein, Franziska (Bristol University Press, 2022)
Using a mixed methods approach, this book examines the role played by regional organisations (ROs) following the occurrence of a coup d'état. It analyses which factors influence the strength of reactions demonstrated by ROs and explores which different post-coup solutions ROs pursue.